POTENSI EKSTRAK BENALU TEH (Scurrula oortiana Dans.) TERHADAP BAKTERI PENYEBAB JERAWAT Staphylococcus epidermidis DAN Staphylococcus aureus - Reubun, Yonathan Tri Atmodjo; Silvyana, Annysa Ellycornia; Warti, Lia; Octaviani, Adinda Tri (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2025)
Acne is a disease in which there is a buildup of skin oil glands which results in clogged skin pores, causing excess fat deposits. Bacteria such as Staphylococcus epidermidis and Staphylococcus aureus are the main factors in the emergence of this acne disease. The use of natural medicine can be used to test the inhibitory activity of both bacteria, one of which is tea mistletoe. The purpose of this study was to obtain the inhibitory activity of bacteria such as Staphylococcus epidermidis and Staphylococcus aureus from tea mistletoe extract using the liquid dilution method, namely MIC and MBC. The concentrations used consisted of 100000ppm, 50000 ppm, 25000ppm, 12500 ppm, 6250ppm, and 3125ppm. The MIC method is based on the turbidity or clarity of the test solution, while the MBC is based on the concentration of the extract in the media used. The results of the study showed that tea mistletoe extract has the potential to inhibit at 50,000ppm and above on both bacteria with the MIC method and kill at a concentration of 50,000ppm on S.aureus bacteria and 25,000ppm on S.epidermidis. The conclusion of this study is that tea mistletoe extract has the potential to inhibit and kill S.epidermidis and S.aureus bacteria at a concentration of 50,000ppm on the MIC and 25,000ppm on the MBC method.